Uncertainty premia in REIT returns. (24th January 2023) - Lotz, Marton; Ruf, Daniel; Strobel, Johannes
Abstract: We provide a systematic study of how financial and real estate uncertainty affect the aggregate return performance of the U.S. REIT market from 1994 to 2017. A temporal causality analysis reveals a negative uncertainty impact on REIT returns. The asset pricing analysis confirms the predictive relation and suggests that REITs are statistically significantly exposed to changes in market‐wide uncertainty, for which investors require a return compensation. We also identify economic state variables to explain time‐varying uncertainty exposures as well as periodic hedging characteristics of REITs. Finally, we find evidence that the source of uncertainty matters for compensating expected REIT returns.